KRIMINALISASI PERS ATAS PUBLIKASI TERHADAP IDENTITAS KORBAN TINDAK PIDANA - Alberth Simanjuntak; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Crime of the Press is a criminal act that publishes news /information about the statement of thoughts or feelings through articles whosecontents are unlawful and may be criminalized. Based on this understanding,the authors formulate two formulation of the problem, namely: First, how theform of criminalization of the press on the publication of the identity of victimsof crime. Second, how is criminal liability for publication of identity of victimsof crime committed by the press.This type of research can be classified in normative legal research(legal research) or also called research literature by examining secondarylegal materials or research based on standard rules that have been recorded isalso called library research, the type of data used is to use secondary dataConsists of primary, secondary and tertiary legal materials. While the datacollection used in this writing is by literature review method or studydukumenter, data that has been collected then processed by way of selection,clarified systematically, logically and juridically qualitatively. The authordraws a deductive conclusion, drawing the conclusions of general matters tospecific matters.From the results of the study there are three main problems that can besummarized as follows: First, provide an understanding especially to theauthor and reader of criminal responsibility publication by the press pursuantto Law No. 40 of 1999 on the Press. Second, to alert the public and the pressabout the rules in publicizing the identity of a person related to criminal law.Third, as a contribution of thoughts and tools to encourage fellow students tocontinue research on the criminalization of the press on the publication of theidentity of victims of crime.Keywords: Criminalization - Press - Publicity - Identity - Victim - Crime